Nuclear energy - Tabak, John. (New York, NY : Facts on File, 2009)
Describes a brief history of Nuclear energy, the way it is produced and used along with arguments for using Nuclear power.
Includes bibliographical references (p. 188-191) and index.
Keywords: Nuclear energy